A Model of Sovereign Debt in Democracies - Alichi, Ali (IMF Working Papers; Working Paper ;, 2008)
This paper develops and empirically tests a political economy model of sovereign debt. The main incentive for repaying sovereign debt is to maintain access to international capital markets. However, in a democracy, one generation may choose default regardless of its consequences for future generations. An old generation with little concern for its country's access to capital markets can force a default on debt if it has the majority of voters. On the other hand, if the younger generation is more numerous, it can force repayment of previously defaulted debt. Other voter heterogeneities, such as in income, can generate similar results.